Novel extrapolation of natural air exposure scenarios in temperate marine intertidal aquaculture using advanced temperature log analysis in R Studio - Ernest O. Chuku; Gregory G. Smith; Debashish Mazumder; Steven A. Rust; Andrew J. Trotter (MethodsX, 2025)
Air exposure influences the physiology and survival of marine intertidal organisms. This study presents a novel, efficient method for quantifying air exposure period using readily available temperature loggers. By leveraging the differential heat capacities of water and air, we developed a thermodynamics-based approach that translates temperature data ( °C) into air exposure estimates (minutes and hours) in a reproducible R Studio workflow. Validation using field data demonstrated successful differentiation of air exposure between low intertidal (1372.6 h, 14 % of culture period) and high intertidal (4157.5 h, 41 %) oyster culture scenarios over a 425-day period (March 2023 - April 2024). Daily and monthly variations in air exposure results further demonstrate our method's sensitivity to changes in tidal cycles and potentially, logger positioning. This approach offers a valuable tool for production management and biological/ecological studies on sessile intertidal marine organisms by providing high-resolution air exposure data. • Time-stamped temperature log data efficiently extrapolates air exposure period based on perpetually submerged subtidal control, and intertidal logger deployments. • Temperature log verification is critical for achieving accurate air exposure estimates. • R Studio programme enables a reproducible workflow for extrapolating air exposure from temperature log data.